The Influence of Product Quality and Price on Purchasing Decisions - Hartini, Ni Made; Oka Setiawan, I Putu (Jurnal Manajemen Pelayanan Hotel, 2023)
In an effort to win business competition, companies must have the right marketing strategy for their products. This study aims to analyze the Effect of Product Quality and Price on Purchasing Decisions at Juice Time Dalung, Badung. Data collection techniques by conducting surveys and interviews. Sampling using the purposive sampling method, namely consumers who have purchased Juice Time products with an age range of 15-45 years and a large sample of 90 respondents. The variables used are product quality variables (X1) and price variables (X2), as well as purchase decision variables (Y). The research method uses multiple linear regression analysis, namely t test and f test with the help of SPSS version 24 for windows. Based on the results of the study, the regression equation Y = -0.508 + 0.484X1 + 0.030X2 was obtained. The hypothetical decision obtained states that partially the product quality variable has a significant effect on the purchase decision, the price variable does not have a significant influence on the purchase decision. However, simultaneously these two variables have a significant influence on the purchase decision of Juice Time Dalung, Badung products. Keywords: Product Quality (X1), Price (X2), Purchase Decision (Y).